2022
DOI: 10.7717/peerj.13047
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA and miRNA profiles of goat bronchial epithelial cells stimulated by Pasteurella multocida strains of serotype A and D

Abstract: Pasteurella multocida (P. multocida) is a zoonotic bacterium that predominantly colonizes the respiratory tract and lungs of a variety of farmed and wild animals, and causes severe respiratory disease. To investigate the characteristics of the host immune response induced by P. multocida strains of serotype A and D, high-throughput mRNA-Seq and miRNA-Seq were performed to analyze the changes in goat bronchial epithelial cells stimulated by these two serotypes of P. multocida for 4 h. Quantitative RT-PCR was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
3
4
0
Order By: Relevance
“…For example, mice challenged with P. multocida serotype D HN01 strain, of which mRNA expression profile showed that I l-10 ( p < 0.05) was significantly up-regulated in the challenge group’s mouse spleen, and results also revealed the high pertinence between I l-10 and the IL-1 family, suggesting the possibly antagonistic regulation of spleen inflammation might exist between them [ 35 ], and this finding was the same as the result of this research. Interestingly, compared with our result, a similar discovery was revealed in another study of goat bronchial epithelial cells stimulated by P. multocida serotype A and D [ 36 ], of which the result indicated that in the P. multocida strain serotype A-stimulated group, the significant KEGG pathways related to immunity were the GABAergic synapse and Toll-like receptor signaling pathway. While in the P. multocida strain serotype D-stimulated group, phagosome and B cell receptor signaling pathway were significantly enriched.…”
Section: Discussionsupporting
confidence: 91%
“…For example, mice challenged with P. multocida serotype D HN01 strain, of which mRNA expression profile showed that I l-10 ( p < 0.05) was significantly up-regulated in the challenge group’s mouse spleen, and results also revealed the high pertinence between I l-10 and the IL-1 family, suggesting the possibly antagonistic regulation of spleen inflammation might exist between them [ 35 ], and this finding was the same as the result of this research. Interestingly, compared with our result, a similar discovery was revealed in another study of goat bronchial epithelial cells stimulated by P. multocida serotype A and D [ 36 ], of which the result indicated that in the P. multocida strain serotype A-stimulated group, the significant KEGG pathways related to immunity were the GABAergic synapse and Toll-like receptor signaling pathway. While in the P. multocida strain serotype D-stimulated group, phagosome and B cell receptor signaling pathway were significantly enriched.…”
Section: Discussionsupporting
confidence: 91%
“…For the RNA−seq experiment, the cells were infected for 6 h with MOI of 100. The reason is that compared with the transcriptome data of the previous P. multocida −infected cells for 4 h with MOI of 100 [ 9 ], it was determined that there were almost no differentially peak-related genes gained from ATAC−seq overlapped with the differentially expressed genes gained from RNA−seq. We speculated that it may take a certain time for gene expression to be transcribed from DNA to RNA.…”
Section: Discussionmentioning
confidence: 99%
“…After the quality detection, the RNA was reverse transcribed and used for cDNA library construction. Sequencing and data analysis were performed as described elsewhere [ 9 , 10 ]. Briefly, the transcriptome data were assembled using StringTie and compared with the reference genome using Hisat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The P. multocida strain of serotype D is usually associated with HS and pneumonia [ 7 ]. Our previous study demonstrated that P. multocida strains of serotypes A (Pm HN02) and D (Pm HN01) led to different cellular morphologies in goat bronchial epithelial cells [ 8 ]. Whether the host immune responses induced by these two strains are different has not been reported.…”
Section: Introductionmentioning
confidence: 99%